IMPROVING NATURAL SCIENCE LEARNING OUTCOMES THROUGH IMAGE MEDIA FOR CLASS II STUDENTS - Sasanti, Nur Rohmah (Universitas Sebelas Maret, 2022)
The research was carried out at SD Negeri 1 Bengking with an implementation time of 2 meetings. The first meeting was on October 28, 2009 and the second meeting was on November 4, 2009. The science subject, sub-subject